2022
DOI: 10.3389/fphar.2022.744038
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Pakistani Physicians' Knowledge and Practices Regarding High Alert Medications: Findings and Implications

Abstract: Introduction: While many low-middle income countries (LMICs), including Pakistan, try and ensure patient safety within available resources, there are considerable concerns with medication use. Unsafe and inappropriate medication use, especially high alert medications (HAMs), is one of the important factors compromising patient safety and quality of care. Besides economic loss, HAMs contribute to greater morbidity, hospitalization, and mortality. Physicians as key members of the provision of healthcare are expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…All participants reported that the questionnaire was clear and easy to understand. The Cronbach’s alpha of this questionnaire was 0.830, showing adequate internal consistency, similar to a previous study ( Mustafa et al, 2022 ). The results from the pilot test were not included in the final analysis of the data.…”
Section: Methodssupporting
confidence: 87%
See 3 more Smart Citations
“…All participants reported that the questionnaire was clear and easy to understand. The Cronbach’s alpha of this questionnaire was 0.830, showing adequate internal consistency, similar to a previous study ( Mustafa et al, 2022 ). The results from the pilot test were not included in the final analysis of the data.…”
Section: Methodssupporting
confidence: 87%
“…The U.S. Food and Drug Administration also warned of the potentially deadly exposure of fentanyl patches in children (Food and Drug Administration, 2021). In addition, 65.7% of the participants agreed with the existence of multiple concentrations to choose from for each drug, which was much higher than the percentage in previous studies (Zyoud et al, 2019;Salman et al, 2020;Mustafa et al, 2022). However, multiple concentrations and multiple dosing options may be potentially serious sources of preventable medication errors, particularly for pediatric patients receiving HAMs (Zyoud et al, 2019;Irwin et al, 2008).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations